Effects Synthetic and Herbal Lysine on Nutritional Value of Local Sesame Seed Meal, Productive Performance and Quality Characteristics of Eggs in Japanese Quail - Amen, Sameerah H.; Al-Jabari, Qana H.; Baker, Ahmed Ghfoor; Shaker, Ahmed S. (American Journal of Biology and Natural Sciences, 2025)
Investigating synthetic and herbal lysine supplementation on local sesame seed meal is crucial for enhancing the nutritional value of quail feed, which can significantly improve the productive performance and egg quality characteristics of Japanese quail. The aimed of the experiment was to study the effect of replacing the sesame male with the soybean meal at different levels by adding synthesis and herbal lysine in the diet of Japanese quail on the egg productivity and egg quality traits such as percentage of hen day, egg mass, feed conversion ration, yolk weight, albumin weight, shell weight, percentage of yolk, percentage of albumin, and percentage of shell. Eighty-four female quail at 45 days of age were used, and divided into seven treatments were as follow included control diet (T1), replacing soybean meal (33%) with sesame seed meal by adding synthetic lysine 1.007 g (T2), replacing soybean meal (66%) with sesame seed meal by adding synthetic lysine 1.010 g (T3), replacing soybean meal (100%) with sesame seed meal by adding synthetic lysine 0.996 g (T4), replacing soybean meal (33%) with sesame seed meal by adding herbal lysine 1.007 g (T5), replacing soybean meal (66%) with sesame seed meal by adding herbal lysine 1.010 g (T6), and replacing soybean meal (100%) with sesame seed meal by adding herbal lysine 0.996 T7, each treatment consists of three replications, and each replication has 4 quails. The productivity traits included (HD%), egg mass (EM), and feed conversion ration were improved significantly by adding the sesame meal, and synthetic lysine. Significant improving were observed between the treatments in yolk weight, albumin weight, and egg shell weight, also their percentages of the egg internal traits (yolk, albumin, and eggshell) were improved significantly. Replacing the soybean meal with sesame meal, by adding the herbal lysine was effectiveeffective on the egg internal traits (yolk, albumin, shell), and also was effectiveeffective on the percentage of (yolk, albumin, shell).